Pengaruh Personal Branding Terhadap Keputusan dan Kepuasan Klien Dalam Menggunakan Jasa Ilustrasi pada Haildi Studio - Nurjanah, Isabela Oktavia; Lumiu, Agnesia Natania (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to determine the influence of personal branding on client decisions and satisfaction when using Haildi Studio's illustration services. The authors used quantitative research and survey methods. A total of 142 clients were sampled using probability techniques. The results are as follows: 1) Haildi Studio's personal branding has been shown to have a positive and significant influence on client decisions when selecting Live2D illustration and rigging services; 2) Haildi Studio's personal branding has been shown to have a positive and significant influence on client satisfaction when selecting Live2D illustration and rigging services; and 3) Haildi Studio's personal branding has been shown to have a positive and significant influence on both client decisions and satisfaction when selecting Live2D illustration and rigging services.